1994
DOI: 10.1289/ehp.94102s965
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of licorice on glycyrrhizin pharmacokinetics.

Abstract: The effects of components of aqueous licorice root extract (LE) on the pharmacokinetics of glycyrrhizin (G) and glycyrrhetic acid (GA) were investigated in rats and humans. The aim of this work was to define the role of pharmacokinetics in G toxicity. In the procedure, G and GA were detected in biological fluids by means of recently improved HPLC methods. Significantly lower G and GA plasma levels were found in rats and humans treated with LE compared to the levels obtained with those in which G alone was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 10 publications
3
27
0
1
Order By: Relevance
“…The metabolism and disposition of GZ in humans and in rats were described in several studies (Wang et al, 1994;Ching et al, 2001Ching et al, , 2002Ozaki et al, 1990;Cantelli-Forti et al, 1994). Previous studies suggested that GZ could be absorbed per se from small intestine and its active metabolite GA was then absorbed from the large intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolism and disposition of GZ in humans and in rats were described in several studies (Wang et al, 1994;Ching et al, 2001Ching et al, , 2002Ozaki et al, 1990;Cantelli-Forti et al, 1994). Previous studies suggested that GZ could be absorbed per se from small intestine and its active metabolite GA was then absorbed from the large intestine.…”
Section: Discussionmentioning
confidence: 99%
“…There were two previous studies reporting the pharmacokinetic difference between pure GZ and licorice in rats and humans (Cantelli-Forti et al, 1994;Ozaki et al, 1990). The results showed that the areas under curves (AUCs) and C max of GZ and GA after dosing with pure GZ were markedly higher than those after dosing with licorice in rats and humans.…”
Section: Introductionmentioning
confidence: 97%
“…They showed a significantly better bioavailability of GL and GA from liquorice than from pure GL in rabbits. In contrast, Cantelli-Forti et al determined lower GL and GA levels in rats after administration of aqueous liquorice root compared with pure GL [27]. Krä [19].…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies [19][20][21] reported that absorption of glycyrrhizin and glycyrrhetinic acid in humans, rabbits, rodents was confirmed by metabolic pharmacokinetics in serum using liquid chromatography-electrospray ionization-mass spectrometry or HPLC, after GR or GRP was consumed. Glycyrrhizin was absorbed per se from the small intestine, and its active metabolite glycyrrhetinic acid was then absorbed from the large intestine.…”
Section: Discussionmentioning
confidence: 93%